Informality on the urban periphery: Housing conditions and self-help strategies in Texas informal subdivisions. (May 2015) - Sullivan, Esther; Olmedo, Carlos
Most scholarship on informal housing focuses on developing countries and little research investigates how low-income populations in the US participate in homeownership through self-built and self-provided housing. Meanwhile, informally developed areas are increasingly being uncovered in the US, especially in the urban periphery of growing metropolitan regions. This paper documents and analyses largely unknown housing conditions and needs for the growing number of people that live in such communities. Data for this paper were collected through a survey of 133 households in two unincorporated low-income, self-help settlements in Central Texas. In this survey we address (1) household composition, (2) specific housing conditions, and (3) reported structural and infrastructural problems. Through regression analyses we identify factors that mitigate or aggravate the severity of overall housing problems and identify the most significant concerns for residents. Our results offer future lines of action regarding property titles, financing and dwelling upgrading.